The Neuroprotective Action of Amidated-Kyotorphin on Amyloid β Peptide-Induced Alzheimer’s Disease Pathophysiology - Belo, Rita F.; Martins, Margarida L. F.; Shvachiy, Liana; Costa-Coelho, Tiago; de Almeida-Borlido, Carolina; Fonseca-Gomes, João; Neves, Vera; Vicente Miranda, Hugo; Outeiro, Tiago F.; Coelho, Joana E.; Xapelli, Sara; Valente, Cláudia A.; et al. (Frontiers in Pharmacology, 2020)
Kyotorphin (KTP, L-tyrosyl-L-arginine) is an endogenous dipeptide initially described to have analgesic properties. Recently, KTP was suggested to be an endogenous neuroprotective agent, namely for Alzheimer's disease (AD). In fact, KTP levels were shown to be decreased in the cerebrospinal fluid of patients with AD, and recent data showed that intracerebroventricular (i.c.v.) injection of KTP ameliorates memory impairments in a sporadic rat model of AD. However, this administration route is far from being a suitable therapeutic strategy. Here, we evaluated if the blood-brain permeant KTP-derivative, KTP-NH2, when systemically administered, would be effective in preventing memory deficits in a sporadic AD animal model and if so, which would be the synaptic correlates of that action. The sporadic AD model was induced in male Wistar rats through i.c.v. injection of amyloid β peptide (Aβ). Animals were treated for 20 days with KTP-NH2 (32.3 mg/Kg, intraperitoneally (i.p.), starting at day 3 after Aβ administration) before memory testing (Novel object recognition (NOR) and Y-maze (YM) tests). Animals were then sacrificed and markers for gliosis were assessed by immunohistochemistry and western blot analysis. Synaptic correlates were assessed by evaluating theta-burst induced long term potentiation (LTP) of field excitatory synaptic potentials (fEPSPs) recorded from hippocampal slices and cortical spine density analysis. In the absence of KTP-NH2 treatment, Aβ-injected rats had clear memory deficits, as assessed through NOR or YM tests. Importantly, these memory deficits were absent in Aβ-injected rats that had been treated with KTP-NH2, which scored in memory tests as control (sham i.c.v. injected) rats. No signs of gliosis could be detected at the end of the treatment in any group of animals. LTP magnitude was significantly impaired in hippocampal slices that had been incubated with Aβ oligomers (200 nM) in the absence of KTP-NH2. Co-incubation with KTP-NH2 (50nM) rescued LTP towards control values. Similarly, Aβ caused a significant decrease in spine density in cortical neuronal cultures, and this was prevented by co-incubation with KTP-NH2 (50nM). In conclusion, the present data demonstrate that i.p. KTP-NH2 treatment counteracts Aβ-induced memory impairments in an AD sporadic model, possibly through the rescuing of synaptic plasticity mechanisms.